2018
DOI: 10.1016/j.enconman.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of E85 versus gasoline as low reactivity fuel for an automotive diesel engine operating in reactivity controlled compression ignition combustion mode

Abstract: This work shows the capabilities of E85 fuel to be used as low reactivity fuel in a high compression ratio light-duty diesel engine (17.1:1) running under reactivity controlled compression ignition concept. To do this, experimental steady-state engine maps are obtained in a single-cylinder engine with diesel-E85 fuel combination. The engine mapping was performed following the same procedure used in previous works with other fuel combinations to allow the results comparison. Considering the mechanical and emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…The two dual-mode concepts studied combine CDC and RCCI combustion regimes to cover the whole engine map. The unique difference between them is the LRF used under RCCI, gasoline [38] or E85 [39]. In both cases, the HRF used is diesel EN590.…”
Section: Dual-mode Strategies Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The two dual-mode concepts studied combine CDC and RCCI combustion regimes to cover the whole engine map. The unique difference between them is the LRF used under RCCI, gasoline [38] or E85 [39]. In both cases, the HRF used is diesel EN590.…”
Section: Dual-mode Strategies Descriptionmentioning
confidence: 99%
“…On the other hand, the low load RCCI region is extended with E85 because of its higher oxygen content compared to gasoline. The extra oxygen content with E85 allows using a higher diesel fraction in the low load region without exceeding the soot limitation, which contributes to reduce the HC and CO levels [39]. In both cases, the RCCI region was completed with NOx and soot emissions levels below 0.4 g/kWh and 0.01 g/kWh, respectively.…”
Section: Dual-mode Strategies Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some approaches have been investigated to overcome these issues and complete the engine map whenever the RCCI is unable to run properly. The low level of geometric and hardware modifications allow switching the combustion mode to, typically, CDC [32]. Nonetheless, such a strategy is difficult to justify from a technological standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies investigated the use of E85 as LRF fuel for RCCI, reporting better or worse indicated efficiencies than using gasoline fuel depending on the operating conditions [48]. In order to understand the main reasons for this difference, a comparison of the energy usage with both fuels at a matched load and CA50 condition is performed in this subsection.…”
Section: E85 Versus Gasolinementioning
confidence: 99%